Influence of oceanographic conditions on nesting abundance, phenology and internesting periods of east Pacific green turtles - Valverde-Cantillo, Verónica (2019)
Sea turtles are migratory animals that travel from foraging grounds to specifc nesting beaches every few years and that, therefore, can be infuenced by oceanographic conditions in several diferent habitats. We assessed how sea surface temperature (SST) and chlorophyll-α (Chl-α) within both internesting and foraging areas infuence the nesting abundance, phenology and duration of internesting periods of the green turtles (Chelonia mydas) that nest at Cabuyal, Northwest Costa Rica. Specifcally, we compared (1) SST and Chl-α in foraging areas to the nesting abundance and median nesting date (MND) registered on the beach over seven nesting seasons and (2) SST in internesting habitats to the observed internesting period (OIP) (number of days between successful nesting events) and the MND. Nesting abundance was strongly correlated to Chl-α concentrations at the main foraging area during the February preceding the nesting season. However, we found no signifcant efect of SST or Chl-α in either foraging or internesting habitats on the MND. Mean SST values in the internesting habitats and OIP were negatively correlated and were highly variable both between and within years. Oceanographic conditions appear to strongly infuence OIP and nesting abundance, but not the nesting phenology of green turtles in this area. The complex nature of the efect of oceanographic conditions on reproduction of the East Pacifc green turtle suggests uncertainty in how this species will respond to climate change